PHOTODYNAMIC THERAPY IN NON SURGICAL TREATMENT OF CHRONIC PERIODONTITIS-A SPLIT MOUTH STUDY - George, Princy Moli; Madhumala, R.; Ravi, Saranyan; Ganesh, N. Sayee; Manovijay, B.; Jayachandran (International Journal of Psychosocial Rehabilitation, 2020)
Chronic periodontitis is a multi-factorial disease due to its complex nature and association with periodontal pathogens. Attempts are made to prevent the progression of the disease at an earlier stage through non-surgical therapy. Many non-surgical modalities have evolved with time with varying degree of success. Hence; the present study was undertaken for assessing the efficacy of photodynamic therapy(PDT) as an adjunct to conventional scaling and root planing in the treatment of moderate chronic periodontitis. Twenty patients diagnosed as chronic periodontitis with recurring probing pocket depth of ≥5mm were included in the study.The study duration was 3 months. In this split mouth study design patients were subjected randomly to scaling and root planing (SRP)alone and in conjunction with diode laser and photosensitizer using Toluidine blue. Photodynamic therapy in conjunction with scaling and root planing was more effective in reducing sulcular bleeding scores, probing pocket depth and clinical attachment loss. Photodynamic therapy is an effective alternative to eradicate microorganisms in periodontal pocket and reducing the clinical parameters which are statistically significant.